Broken heartstrings: post-traumatic stress disorder and psychological burden after acute mitral regurgitation due to chordae tendineae rupture - Cranz, Anna; Greinacher, Anja; Nagy, Ede; Friederich, Hans-Christoph; Katus, Hugo; Geis, Nicolas; Pleger, Sven Torsten; Nikendei, Christoph (Journal of Clinical Medicine, 2020)
Chordae tendineae rupture (CTR) is a potentially life-threatening cardiac event often resulting in Acute mitral regurgitation (AMR). We assessed Post-traumatic stress disorder (PTSD), depression, and anxiety symptoms in n=21 CTR patients with AMR (age 82.3 ± 4.2 years; 66.7% men) and compared them to n=23 CTR patients with Chronic mitral regurgitation (CMR) and n=35 Myocardial infraction (MI) patients. Regression analyses revealed that PTSD scores were significantly higher in CTR patients with AMR than in CTR patients with CMR or MI patients. CTR patients with CMR had the lowest levels of PTSD-symptoms. Depression and anxiety scores were elevated across all three groups. Our results suggest that psychosocial factors need to be considered in CTR patients’ care.